STAS Domain Only Proteins in Bacterial Gene Regulation - Moy, Brian E.; Seshu, J. (Frontiers in Cellular and Infection Microbiology, 2021)
Sulfate Transport Anti-Sigma antagonist domains (Pfam01740) are found in all branches of life from eubacteria to mammals as a conserved fold encoded by highly divergent amino acid sequences. These domains are present as part of larger SLC26/SulP anion transporters, where the STAS domain is associated with transmembrane anchoring of the larger multidomain protein. Here, we focus on STAS Domain only Proteins (SDoPs) in eubacteria, initially described as part of the B. subtilis Regulation of Sigma B (RSB) regulatory system. Since its initial description in B. subtilis, SDoPs have been described to be involved in the regulation of sigma factors through partner switching in various bacteria such as: M. tuberculosis, L. monocytogenes, V. fischeri, B. bronchiseptica, among others. In addition to playing a canonical role in partner switching with an Anti-Sigma factor to affect the availability of a Sigma factor, several of eubacterial SDoPs show additional regulatory roles compared to the original RSB system of B. subtilis. This is of great interest as these proteins are highly conserved, and often involved in altering gene expression in response to changes in environmental conditions. For many of the bacteria examined here the ability to sense environmental changes and alter gene expression accordingly to survive is critical for host colonization and therefore SDoPs are intrinsically linked to virulence.